The Prevalence and Risk Factors of Musculoskeletal Disorders among Burmese Migrant Labor in Thailand - , Parvena Meepradit (Archives of Current Research International, 2016)
Introduction: Work-related musculoskeletal disorders (WMSDs) are significant problems in Thailand. However, only limited researches have been conducted on the situation concerning migrant workers. Therefore, to achieve equality in health surveillance for migrant people, this research has been aimed at investigating the prevalence and risk factors associated with the musculoskeletal system among the migrant workers in Samut Sakhon province. Methodology: A cross sectional study was conducted randomly on all 303 Burmese workers. A self-administered questionnaire was used for recording the socio-demographic data, risk factors and musculoskeletal symptoms among the samples. Results: The prevalence of musculoskeletal disorders having the most commonly reported complaints concerned with the low back reaching at 47.9% , followed by the shoulder with 41.6%, upper back 37.0%, neck 34.0%, hand / wrist 20.5%, knee 17.5%, thigh 17.2%, ankle / foot 16.8%, and elbows 10.6% respectively. Most of the symptoms were defined as pain occurring in the past 7 days. Moreover, the results pointed out that the personal and work-related factors associated with the musculoskeletal disorders were significant. Conclusion: From the results, it should be suggested that effective intervention strategies, most likely, have to be taken into account for both demographic and ergonomic factor aspects.